2014
DOI: 10.1016/j.ecolind.2013.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of size, weight, body compartment, sex and reproductive status on the bioaccumulation of 19 trace elements in rope-grown Mytilus galloprovincialis

Abstract: a b s t r a c tNumerous trace elements (TEs) can be considered as potential pollutants of the environment, their mining productions and industrial uses increasing worldwide. Their monitoring can be achieved through the use of bioindicator species, such as the Mediterranean mussel Mytilus galloprovincialis (Lamarck, 1819). That species has been widely used to monitor the chemical pollution of coastal ecosystems by Cr, Ni, Cu, Zn, Cd, Pb, As, Ag and V. Conversely, environmental levels of Be, Al, Fe, Mn, Co, Se, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 49 publications
0
21
1
3
Order By: Relevance
“…This pattern could be found in Cu, Zn, Cd and Pb, and the former three metals showed a significantly negative correlation ( p < 0.05) with GSI. Several studies have described a resting phase maximum and summer pre‐spawning minimum of metal concentration in oysters, clams and mussels (Adjei‐Boateng, Obirikorang, Amisah, Madkour, & Otchere, ; Fŕias‐Espericueta et al, ; Lobe1, & Wright, ; Páez‐Osuna et al, ; Richir & Gobert, ). However, in these investigations, correlations between GSI and metal concentrations in the gonad were relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern could be found in Cu, Zn, Cd and Pb, and the former three metals showed a significantly negative correlation ( p < 0.05) with GSI. Several studies have described a resting phase maximum and summer pre‐spawning minimum of metal concentration in oysters, clams and mussels (Adjei‐Boateng, Obirikorang, Amisah, Madkour, & Otchere, ; Fŕias‐Espericueta et al, ; Lobe1, & Wright, ; Páez‐Osuna et al, ; Richir & Gobert, ). However, in these investigations, correlations between GSI and metal concentrations in the gonad were relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…If we consider that ST is indicative of age (Frew et al, 1989), the accumulation of these organic molecules would be higher in younger individuals, which could be related to its higher activity compared with older individuals (Yap et al, 2003). In a similar way, it has been described that animal size clearly influences bioaccumulation of chemical compounds in bivalves where higher concentrations was observed in smaller individuals (Richir and Gobert, 2013). The effect of animal size on pollutant bioaccumulation, have been related to variations in physiological processes, as feeding, which depends of size and age (Zhong et al, 2013).…”
Section: Pollutionmentioning
confidence: 93%
“…Such data highlight the importance of separate MAO activity analysis across sex, especially because sex of the mussel can impact metal accumulation . Richir and Gobert showed that Mn and Cd, but not Pb, metal concentrations vary across sex in Mytilus galloprovincialis , highlighting the importance of sex identification in metal exposure studies.…”
Section: Discussionmentioning
confidence: 97%